Legal Regulation of Forensic Autopsies in the Criminal Investigation Process: A Study of Concepts and Legal Reform - Subhandi Bakhtiar, Handar (Journal of Law, Politic and Humanities, 2024)
In criminal justice, forensic autopsies play a critical role in determining the cause and manner of death. Current provisions are unclear, leading to inconsistencies in the criminal investigation process. This study examines weaknesses in Indonesian law, particularly the ambiguity in regulating forensic autopsies, the obligation to conduct autopsies in suspected criminal deaths, and the procedures for notifying the victim's family. This study aims to provide an interpretation of the legal regulations concerning autopsies and to formulate regulatory reforms related to the conduct of autopsies in criminal investigation processes. The results of this study indicate that in criminal investigations, autopsies are crucial for determining the cause and manner of death, as well as providing scientific evidence linking the perpetrator's actions to the victim's death. However, ambiguity in interpreting the obligation to conduct autopsies under Article 134 of the Criminal Procedure Code (KUHAP) leads to inconsistencies. To address this, clear regulations are needed to define when an autopsy is considered "very necessary," providing consistent guidance to investigators. Mandatory autopsies for all unnatural deaths would ensure thorough examinations. While families must be informed, their consent is not required, and obstructing an autopsy is a criminal offence, supported by Article 222 of the Criminal Code, as amended by Article 283 of Law No. 1 of 2023 concerning the Criminal Code.